Aktivitas Antifungi Fraksi Etilasetat Akar Singawalang (Petiveria alliacea L.) terhadap Aspergillus niger - Niken Indriyanti (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2015)
Aspergillus niger is a mold that can infect respiratory tract in certain condition. Azoles are used to solve this infection. Drug development on antifungal drugs still continued, one of the resorce is from plant. A plant that widely studied as antifungi is singawalang (Petiveria alliacea L.). Activity of ethanol extract and fraction of singawalang roots on Aspergillus niger tested by microdilution broth method appropriate to Clinical and Laboratory Standard Institute (CLSI) standard. Microdilution test results showed that Singawalang roots extract has antifungal activity against Aspergillus niger with Minimum Inhibition Concentration (MIC) 32 Î¼g/mL and Minimum Fungicidal Concentration (MFC) 1048 Î¼g/mL. Fraction that has high activity against Aspergillus niger was ethylacetate fraction of Singawalang roots with MIC 128 Âµg/ml dan MFC 512 Î¼g/mL. The higher activity of the extract than the fraction was predicted as the impact of multiple compounds that have synergic activity. The growth profile of Aspergillus niger showed unconstant result and tends to descend. However, further research needed to ensure this effect. Keywords: antifungal, microdilution, singawalang (Petiveria alliacea L.), Aspergillus niger ABSTRAK Aspergillus niger merupakan kapang penginfeksi saluran pernafasan pada kondisi tertentu. Obat-obat golongan azol biasa digunakan untuk mengatasi infeksi ini. Pengembangan obat antifungi saat ini terus dilakukan, termasuk dari tanaman. Salah satu tanaman yang telah banyak diteliti memiliki efek antifungi adalah tanaman singawalang (Petiveria alliacea L.). Pengujian dilakukan dengan Broth Microdilution sesuai standar Clinical and Laboratory Standard Institute (CLSI). Ekstrak akar singawalang menghambat pertumbuhan Aspergillus niger dan memiliki KHM 32 ppm dan KFM 1048 ppm. Hasil dan Fraksi Ekstrak Akar Singawalang Terhadap Aspergillus niger pada fraksi etilasetat ekstrak etanol akar singawalang adalah Konsentrasi Hambat Minimum (KHM) 128 Î¼g/mL dan Konsentrasi Fungisidal Minimum (KFM) 512 Î¼g/mL. KHM ekstrak yang lebih tinggi diduga karena senyawa yang bekerja sinergis. Profil pertumbuhan Aspergillus niger tidak konstan dan cenderung menurun mirip efek fungisida sehingga penelitian lanjutan diperlukan untuk memastikan efek tersebut. Kata Kunci: Antifungi, mikrodilusi, singawalang (Petiveria alliacea L.), Aspergillus niger